PENGARUH DOSIS DAN LAMA PEMBERIAN EKSTRAK DAUN ASAM JAWA (TAMARINDUS INDICA LINN) TERHADAP HOMA-Β PADA TIKUS MODEL DIABETES MELLITUS TIPE 2 The eﬀect of Tamarind Leaf (tamarindus indica linn) Extract on HOMA-β in Rats with Type 2 Diabetes Mellitus Model - Devi Novia; Sugiarto Sugiarto; Yulia Lanti Dewi (Media Gizi Indonesia, 2021)
Nowadays the epidemiological burden of diabetes increases with long life-threatening symptoms and the eﬀects      of antidiabetic drugs. Lack of insulin activity is one of the signs of a drop in diabetes mellitus. The mechanisms in antidiabetic include stimulating β-Langerhans cells which secrete insulin and inhibit enzyme activity. The purpose of this study was to analyze the eﬀect of giving tamarind leaf extract on levels of homa-β in type 2 diabetes mellitus rats. This study used 30 male Wistar rats aged 8-12 weeks with a bodyweight of 150-200 grams and separated into 5 groups. The first group is KN group (DMT2 mice + standard diet), group 2 is KP (DMT2 + Acarbose mice), group 3 is P1 (DMT2 mice + tamarind leaf extract 28 mg / 200gr / day), group 4 is P2 (rat DMT2 + tamarind leaf extract 56 mg/200gr/day), and group 5 is P3 (DMT2 rat + tamarind leaf extract 112 mg / 200gr / day). The measurement method for Homa-β is to use a standardized formula and use the results of blood tests for fasting blood glucose and insulin levels. The results of the inter-variable study using one-way Anova found a significant diﬀerence between the levels of homa-β and the administration of tamarind leaves extract in rats with type 2 diabetes mellitus model (p <0.05). There were significant diﬀerences in the 5 treatment groups. On the 7th day, there was an increase in homa-β levels in the KP, P1, P2, and P3 groups while in the KN group decreased in homa-β levels. The P3 group was seen to have the highest increase in homa-β levels in the 14th day, but on the 14th day there was no significant diﬀerence between the acarbose drug group (99.57 ± 6.41) and the P3 group (15.09 ± 1, 71). The conclusion was the administration of tamarind extract at a dose of 28.56, and 112 mg/kgBW/day significantly increased levels of HOMA-β for 7 and 14 days in rats with type 2 diabetes mellitus.